The Pol Pot regime : race, power, and genocide in Cambodia under the Khmer Rouge, 1975-79 - Kiernan, Ben (New Haven [Conn.] : Yale University Press, 2008)
This edition of Ben Kiernan's account of the Cambodian revolution and genocide includes a new preface that takes the story up to 2008 and the UN-sponsored Khmer Rouge tribunal. Kiernan's other books include 'Blood and Soil: A World History of Genocide and Extermination from Sparta to Darfur' and 'How Pol Pot Came to Power'.
CHAPTER ELEVEN: The End of the Pol Pot RegimeSelect Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z -- Photos and maps
Includes bibliographical references (pages 467-469) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Parti communiste du Kampuchea; Pol Pot; Pol, Pot; Parti communiste du Kampuchea; Cambodia -- Politics and government -- 1975-1979.; Communism -- Cambodia; Political atrocities -- Cambodia; Genocide -- Cambodia; Cambodge -- Politique et gouvernement -- 1975-1979.; Atrocités politiques -- Cambodge; HISTORY; HISTORY -- Asia -- Southeast Asia; Communism; Genocide; Political atrocities; Politics and government; Cambodia; 1975-1979